2011
DOI: 10.1029/2010gl046056
|View full text |Cite
|
Sign up to set email alerts
|

The effect of continents on mantle convective stirring

Abstract: [1] We have investigated the influence of continental lids on mantle convective stirring efficiency using numerical experiments and analytical theory at infinite Prandtl number with strong temperature dependence of viscosity. Differences between oceans and continents are accounted for by imposing heterogeneous surface boundary conditions for temperature and velocity. We measure the convective stirring efficiency using mixing times and Lyapunov exponent distribution. We quantify systematically the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Each diagram is divided in two domains according to the time of onset of convection in the simulations (early or late onset). As expected, the reference Rayleigh number has a clear monotonic influence on the onset of convection and on the degree of mixing [Samuel et al, 2011;Samuel and Tosi, 2012]. However, the dependence of the final value of the shrinking factor on the buoyancy ratio B and on the solidification time t MO is more complex.…”
Section: Early and Late Onset Of Convection And Mixingsupporting
confidence: 69%
See 1 more Smart Citation
“…Each diagram is divided in two domains according to the time of onset of convection in the simulations (early or late onset). As expected, the reference Rayleigh number has a clear monotonic influence on the onset of convection and on the degree of mixing [Samuel et al, 2011;Samuel and Tosi, 2012]. However, the dependence of the final value of the shrinking factor on the buoyancy ratio B and on the solidification time t MO is more complex.…”
Section: Early and Late Onset Of Convection And Mixingsupporting
confidence: 69%
“…Low values of σ − indicate stronger shortening of mantle parcels with larger aspect ratio, favoring mixing and homogenization with the surroundings via chemical diffusion [ Olson et al , ; Gurnis , ; Ottino , ]. Equivalently, this quantity expresses the amount by which the initial size of a mantle parcel has been reduced as a result of the deformation along its trajectory [ Samuel et al , ; Samuel and King , ]. In other words, for a mantle parcel of given initial size δ 0 , its dimension in the direction of maximum shrinking at time t is just δ = δ 0 σ − , implying that the smaller the σ − , the more efficient is mixing.…”
Section: Modelmentioning
confidence: 99%
“…For instance, with scriptB=0, the scaling we derived for constant viscosity predicts that a reduction of R a by one order of magnitude determines an increase of the mixing time by approximately a factor of 3.2. This result compares relatively well with the findings of Samuel et al [] who preformed a similar calculation (i.e., isoviscous fluid in 2‐D Cartesian geometry with aspect ratio of four assuming scriptB=0) and estimated mixing times through a more sophisticated Lagrangian technique. They found that, independently of the wavelength of heterogeneity considered, the mixing time obtained with R a =10 6 is about four times larger than that obtained with R a =10 7 , which confirms the validity of our simple approach based on relative differences in the laterally averaged profile of the composition field.…”
Section: Discussionmentioning
confidence: 99%
“…Our description based on equation , however, was sufficient for our purposes. Indeed, a comparison of the effects of the Rayleigh number on mixing times with the results of Samuel et al [] confirmed the validity of our approach (see Figure and section 4.1).…”
Section: Model and Methodsmentioning
confidence: 99%
“…The underlying physics of those interactions can nevertheless be perceived by numerical investigations of the mechanical and thermal coupling between insulating lids and mantle flow. Various studies show that continents may create long wavelength patterns in the convective layer [ Phillips and Bunge , 2005; Grigné et al , 2007a, 2007b] while raising the temperature beneath supercontinents [ O'Neill et al , 2009; Phillips and Coltice , 2010] and in turn enhancing convective vigor for temperature‐dependent viscosity models [e.g., Lenardic et al , 2005; Samuel et al , 2011]. Furthermore, time‐dependent simulations show that continental insulation leads to mantle overheating and to aggregation and dispersal of supercontinents [ Gurnis , 1988].…”
Section: Introductionmentioning
confidence: 99%